CULTURAL TOURISM STRATEGIES OF INDIA: AN OVERVIEW - Prajapati, Satyendra; Kumar, Sandip (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India has come up as a great cultural tourism hub revealing to the visitor delightful hospitality, history, arts, architecture, culture and festivals. This paper gives a general view of cultural tourism section in the Indian context particularly covering the cultural tourism management of India’s cultural heritage. The paper explores the measures that have been taken by the government, private sector, and community in the promotion of cultural tourism as a sustainable and economic development tool. The paper aims at especially focusing on historical and religious sites and artwork as the ways thru which to establish the overall challenges of achieving the balance between tourism and culture. Also, it addresses the part of digital opportunity, marketing, and partnership in promoting India’s cultural products and services to the world. According to this paper, India’s cultural tourism needs to have sound economic and strategic planning that involves communities to enhance the development of culture tourism without degrading the cultures.